FACTORS AFFECTING THE INTENTION TO CONTINUE STUDYING AT MASTER LEVEL OF STUDENTS AT INDUSTRIAL UNIVERSITY OF HOCHIMINH CITY - Hồ Trúc Vi; Phan Trọng Nhân (Tạp chí Khoa học Đại học Đà Lạt)
This article deals with an analysis of the factors affecting the intention to continue studying at master level of students at Industrial University Hochiminh City (IUH) on the basis of a survey conducted for 432 students at this university. The study shows that four factors: Behavioral control; Brand loyalty; Attitude toward behavior; and Subjective norm have the positive effect on IUH student’s intention. This is also the impact level in descending order of the 4 factors affecting to IUH student’s intention.